(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
’Compare’ is the instinctual propensity of the individual to assess his own actions vis-à - vis the others. He’s really involved in learning how people work, interact and act around him. Contemporary political science is key to a thesis on international politics. Consequently, comparative policy has been an field of growing interest in all nations. New Social Sciences lately have expanded our capacity to track and routinely analyses the analytical universe of reality surrounding us and to make conceptual calculation and rational and quantitative interpretation equal to numerical facts and processes. The behavioral sciences have also presented us with much new, loosely validated knowledge about how individuals internally and as a group think, behave, interpret and conduct. We will first describe the word comparative and then legislation before we try to establish ’compare’ regulation.